Cellulose nanofiber aerogel as a promising biomaterial for customized oral drug delivery - Bhandari, Jyoti; Mishra, Harshita; Mishra, Pawan Kumar; Wimmer, Rupert; Ahmad, Farhan J; Talegaonkar, Sushama (International journal of nanomedicine, 2017)
Cellulose nanofiber (CNF) aerogels with favorable floatability and mucoadhesive properties prepared by the freeze-drying method have been introduced as new possible carriers for oral controlled drug delivery system. Bendamustine hydrochloride is considered as the model drug. Drug loading was carried out by the physical adsorption method, and optimization of drug-loaded formulation was done using central composite design. A very lightweight-aerogel-with-matrix system was produced with drug loading of 18.98%±1.57%. The produced aerogel was characterized for morphology, tensile strength, swelling tendency in media with different pH values, floating behavior, mucoadhesive detachment force and drug release profiles under different pH conditions. The results showed that the type of matrix was porous and woven with excellent mechanical properties. The drug release was assessed by dialysis, which was fitted with suitable mathematical models. Approximately 69.205%±2.5% of the drug was released in 24 hours in medium of pH 1.2, whereas ~78%±2.28% of drug was released in medium of pH 7.4, with floating behavior for ~7.5 hours. The results of in vivo study showed a 3.25-fold increase in bioavailability. Thus, we concluded that CNF aerogels offer a great possibility for a gastroretentive drug delivery system with improved bioavailability.
Keywords: dialýza; Drug Delivery Systems; bendamustin hydrochlorid; Nanofibers; mucoadhesion; lyofilizace; Cellulose; celulosa; Rats, Wistar; koncentrace vodíkových iontů; Bendamustine Hydrochloride; floating behavior; biologická dostupnost; biokompatibilní materiály; Biological Availability; ženské pohlaví; Freeze Drying; aerogel; uvolňování léčiv; bioavailability; controlled release; Biocompatible Materials; swelling behavior; Administration, Oral; mužské pohlaví; pevnost v tahu; aplikace orální; Animals; Hydrogen-Ion Concentration; cellulose nanofiber; lékové transportní systémy; nanovlákna; Dialysis; nosiče léků; Female; Drug Liberation; gastroretentive; potkani Wistar; Male; zvířata; Tensile Strength; Drug Carriers